Nutritional value and antioxidant compounds during the ripening and after domestic cooking of bananas and plantains. (June 2020) - Borges, C.V.; Maraschin, M.; Coelho, D.S.; Leonel, M.; Gomez, H.A.G.; Belin, M.A.F.; Diamante, M.S.; Amorim, E.P.; Gianeti, T.; Castro, G.R.; Lima, G.P.P.
Graphical abstract: Highlights: Plantains and cooking bananas presented a high content of resistant starch. Peel showed superior phenolic compounds and minerals levels than pulp. Ripe dessert and cooking banana presented high values of phenolic compounds. Catechin and quercetin contributed strongly to the antioxidant activity of the Musa spp. Boiling with peel increased the phenolic compounds of Musa spp. fruit. Abstract: Genotypes of bananas and plantains have been studied for biofortification purposes, mainly due to content of resistant starch (RS) and polyphenols. This study aims to identify banana and plantain genotypes with a high content of resistant starch, phenolic compounds and minerals, and to evaluate the impact of the ripening stage and domestic thermal processing to select superior genotypes with high levels of functional compounds. In this study, it was used bunches of bananas and plantain genotypes. The phenolic compounds profiles were determined by HPLC-DAD in pulps and peels. The resistant starch and the minerals (K, Na, Zn, Cu and Fe) were evaluated in pulps and peels of unripe fruit. The results of phenolic compounds were studied in three ripening stages, and after thermal processing (ripe stage) of two genotypes, which were most promising for biofortification studies. Resistant starch and minerals were analysed in the unripe fruits. The peel biomass showed the highest values of phenolic compounds and minerals. The total starch content in the pulp varied from 42.3% ('FC06-02′) to 80.6% ('Pelipita'). Plantains and cooking bananas presented the highest contents of starch and resistant starch (stage 2 – green with yellow traces). The pulps of the dessert genotypes 'Khai' and 'Ouro da Mata', and cooking genotype 'Pacha Nadam' stood out due to their minerals high contents (P, K and Fe; Zn and Fe; Ca, Mg and Zn, respectively). The dessert bananas (e.g., 'Ney Poovan') and cooking bananas (e.g., 'Tiparot') had the highest concentrations of phenolic compounds, mainly in ripe fruit (stage 5 – yellow with green). In addition, the thermal processing of Musa spp. fruit led to increasing these secondary metabolites, mainly the cooking of fruit with peel by boiling, which should be preferred in domestic preparations.